Dual modulation of nitric oxide production in the heart during ischaemia/reperfusion injury and inflammation - Darra, Elena; Rungatscher, Alessio; de Prati, Alessandra Carcereri; Podesser, Bruno K.; Faggian, Giuseppe; Scarabelli, Tiziano; Mazzucco, Alessandro; Hallström, Seth; Suzuki, Hisanori (Thrombosis and Haemostasis, 2010)
Nitric oxide (NO) homeostasis maintained by neuronal/endothelial nitric oxide (NO) synthase (n/eNOS) contributes to regulate cardiac function under physiological conditions. At the early stages of ischaemia, NO homeostasis is disturbed due to Ca2+-dependent e/nNOS activation. In endothelial cells, successive drop in NO concentration may occur due to both uncoupling of eNOS and/or successive inhibition of nNOS catalytic activity mediated by arachidonic acid-induced tyrosine phosphorylation of this enzyme. The reduced NO bioavailability triggers nuclear factor (NF)-κB activation followed by the induction of inducible NOS (iNOS) expression. In cardiomyocytes ischaemia also triggers the induction of iNOS expression during reperfusion. The massive amounts of NO which are subsequently produced following iNOS induction may exert on cardiomyocytes and the other cell types of cells of the heart, such as endothelial and smooth muscle cells, macrophages and neutrophils, opposing effects, either beneficial or toxic. The balance between these two double-faced actions may contribute to the final clinical outcomes, determining the degree of functional adaptation of the heart to ischaemia/reperfusion injury. In the light of this new vision on the critical role played by the cross-talk between n/eNOS and iNOS as well as the non enzymatic NO production by nitrite, we have reason to believe that new pharmacological measurements or experimental interventions, such as ischaemic preconditioning, aimed at counteracting the drop in NO levels beyond the normal range of NO homeostasis during early reperfusion can represent an efficient strategy to reduce the extent of functional impairment and cardiac damage in the heart exposed to ischaemia/reperfusion injury.
Keywords: Cardiology; ischaemic heart disease; nitric oxide/NO